Quality of life and anxiety in women with breast cancer before and after treatment - Raquel Rey Villar; Salvador Pita Fernández; Carmen Cereijo Garea; Mª Teresa Seoane Pillado; Vanesa Balboa Barreiro; Cristina González Martín (Universidade de São Paulo, 2017)
ABSTRACT Objectives: to determine the quality of life and anxiety in patients with breast cancer and the changes they experience after treatments. Method: prospective study. Breast cancer statistics (n=339, confidence=95%, accuracy= ± 5.32%). The quality of life questionnaires (QLQ) used were QLQ C-30 and QLQ Br23, and the State-Trait Anxiety Inventory (STAI) was used for anxiety. A multivariate analysis was performed to identify variables associated with baseline quality of life and anxiety as well as pre- and post-treatment differences. Authorization was obtained from the Ethics Committee, and informed consent was provided by all patients. Results: the baseline quality of life dimensions with the lowest score were future prospects (46.0/100) and sexual enjoyment (55.7/100). The dimensions with the highest score were body image (94.2/100) and role (93.3/100). The most disturbing symptoms were insomnia, fatigue and concern about hair loss. After treatment, the dimensions of physical function, role, body image, financial concerns and symptomatology worsened, whereas emotional function and future prospects improved. Severe anxiety presented as a state (48.6%) and as a trait (18.2%). The highest baseline state anxiety was associated with married-widowed status and anxiolytic medication. The greatest trait anxiety was associated with an inactive work situation, anxiolytic medication, breast swelling and advanced stage at diagnosis. After treatment, anxiety significantly decreased. Conclusions: After treatment, the quality of life score was positively modified, while state and trait anxiety decreased.